The Role of Artificial Intelligence in Enhancing the Cyber Notary Concept in the Digital Era: Opportunities, Challenges, and Implications - Dio Ahmad Hafidzan; Isis Ikhwansyah; Nanda Anisa Lubis; Yassine Chami (Universitas Negeri Semarang, 2026)
The rapid advancement of Artificial Intelligence (AI) is reshaping the landscape of legal services, with particular consequences for the practice of notarization. The concept of the Cyber Notary, a digital notarial service enabling remote and secure authentication of legal documents, has emerged as a critical institutional innovation in response to growing demand for efficient digital legal infrastructure. Yet, despite its transformative potential, the integration of AI into Cyber Notary systems continues to generate unresolved tensions between technological capability and legal permissibility. This study examines the role of AI in strengthening the Cyber Notary concept in the digital era, with particular emphasis on Indonesia's normative framework. Through a normative legal research methodology combining statutory, comparative, and conceptual approaches, this paper identifies a fundamental conflict between the physical-presence requirements embedded in Law Number 2 of 2014 on Notarial Positions (UUJN) and the digitalization imperatives recognized under the ITE Law and Law Number 27 of 2022 on Personal Data Protection (PDPL). Drawing on comparative insights from Japan, the European Union, and the United States, the study demonstrates that the adoption of AI in notarial practice is legally feasible only where supportive regulatory infrastructure exists, a condition that Indonesia has not yet fully met. The findings underscore the necessity of targeted legislative reform, enhanced algorithmic transparency, and formal professional guidance to bridge the current regulatory vacuum. This research contributes to the broader discourse on the responsible integration of AI in civil law jurisdictions, offering concrete recommendations for policymakers, legal practitioners, and technology developers.